(3JNdjU GdEfSGf ef XdeGJ GdONGfs
(3ChdgG (B:s
(3SjO GdeQSdjf hYdi Bdg CaVd GdUdhGJ hSejJg HJNdjU GdEfSGf ef XdeGJ GdONGf s
(3BNQgG (B:s
(3dYd Gddg jJhH YdjfG hjMTQfG ai ReQI GdUdMGA hGdebQHjf HMQeI SjO GdeQSdjf hNGJe GdfHjjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdESdGejs